Rencana Bisnis Aksesoris PALM's Craft - Nursiska, Lena; Annastasia, Marizka; Andriani, Putri Rizki; Rachmawati, Sofa; Munira, Tsurayya; Suwandi, Suwandi (Journal of Entrepreneurship, Management and Industry (JEMI), 2018)
Fashion becomes an indispensable part of everyday looks and style. Objects such as clothing, accessories and styles worn are not just body coverings and ornaments, but rather as a form of non-verbal communication tool in conveying a personal identity or group identity. This final project journal contains a summary of the "PALM'S Craft" business plan in the fashion accessories world of bracelets, from business processes to development plans for the coming year. The analysis includes analysis of marketing strategy, SWOT, and pricing. In its development plan, it also contains some financial information related to "PALM'S Craft", as well as information on funding and profit and loss "PALM'S Craft".